The Endocannabinoid/Endovanilloid System and Depression - Smaga, Irena (Curr Neuropharmacol, 2014)
Depression is one of the most frequent causes of disability in the 21st century. Despite the many preclinical and clinical studies that have addressed this brain disorder, the pathophysiology of depression is not well understood and the available antidepressant drugs are therapeutically inadequate in many patients. In recent years, the potential role of lipid-derived molecules, particularly endocannabinoids (eCBs) and endovanilloids, has been highlighted in the pathogenesis of depression and in the action of antidepressants. There are many indications that the eCB/endovanilloid system is involved in the pathogenesis of depression, including the localization of receptors, modulation of monoaminergic transmission, inhibition of the stress axis and promotion of neuroplasticity in the brain. Preclinical pharmacological and genetic studies of eCBs in depression also suggest that facilitating the eCB system exerts antidepressant-like behavioral responses in rodents. In this article, we review the current knowledge of the role of the eCB/endovanilloid system in depression, as well as the effects of its ligands, models of depression and antidepressant drugs in preclinical and clinical settings.